Implementation of Padang City Regional Regulation Number 8 of 2019 Concerning Parking Operations" - Yola Oktaviana; Adil Mubarak (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study was conducted to describe how the implementation of Padang City Regional Regulation No. 8 of 2019 concerning Parking Implementation. The purpose of this study is to see how the implementation of Padang City Regional Regulation No. 8 of 2019 concerning Parking Implementation. The type of research used is qualitative research with descriptive methods. The selection of research informants used the Purposive Sampling technique, research data was obtained from the results of interviews with related informants, direct observation of parking in the road space in Padang City and documentary evidence and data in the form of documents at the Transportation Service and UPT Parking Padang City. Data analysis in this study uses data reduction, data presentation, conclusions and verification. The results of the study indicate that the Implementation of Padang City Regional Regulation No. 8 of 2019 concerning Parking Implementation has met each indicator, but there are still problems in its implementation, namely from the Size and Objectives of the Policy factors where parking officers do not fully understand the objectives of this Regional Regulation which can be seen from non-compliance in the use of parking attributes, then from the Human Resources factor which is lacking in quantity in its implementation, finally from the Social, Economic and Political Environment factors that do not run as expected, the social environment is not sensitive to the rules and parking officers who play with certain Department officials.